Assessment and determinants of global outcomes among 445 mass-casualty burn survivors: A 2-year retrospective cohort study in Taiwan. Issue 6 (September 2020) - Ma, Hsu; Tung, Kwang-Yi; Tsai, Shu-Ling; Neil, David L.; Lin, Yun-Yi; Yen, Hung-Tsang; Lin, Kao-Li; Cheng, Yi-Ting; Kao, Shu-Chen; Lin, Mei-Na; Dai, Niann-Tzyy; Perng, Cherng-Kang; et al.
Highlights: Follow-up of 445 flash fire survivors revealed key determinants of long-term outcomes. Mean TBSA was 41%, mean hospital stay 63 days, and rehabilitation duration 51 weeks. After 2 years, 225 people had impaired skin function: 118 mild, 73 moderate, 34 severe. Besides %TBSA, burn depth and scar contractures also determined functional recovery. The most severe burns accounted for <10% of costs; 41–80% TBSA accounted for 73.2%. Abstract: Purpose: To study outcomes among survivors of the mass-casualty powder explosion on 27 June 2015, at Formosa Fun Coast Waterpark, New Taipei City, Taiwan. Methods: Using retrospective data on Taiwanese survivors, we analyzed prehospital management, burns assessment and prognosis, functional recovery, and medical costs, followed-up through 30 June 2017. We related outcomes to burn extent, categorized according to the percentages of total body surface area with second/third-degree burns (%TBSA) or autologous split-thickness skin grafts (%STSG), and an investigational scale: f SASG = (%TBSA + %STSG)/2, stratified by %STSG. Analyses included casualty dispersal, comparisons between %TBSA, %STSG and f SASG, and their relationships with length of hospitalization, times to rehabilitation and social/school re-entry, physical/mental disability, and medical costs. We also investigated how burn scars restricting joint mobility affected rehabilitation duration. Results: 445 hospitalized casualties (excluding 16 foreigners, 23 with 0% TBSA and 15 fatalities) aged 12–38 years, had mean TBSA of 41.1%. Hospitalization and functional recovery durations correlated with %TBSA, %STSG and f SASG – mean length of stay per %TBSA was 1.5 days; more numerous burn scar contractures prolonged rehabilitation. Females had worse burns than males, longer hospitalization and rehabilitation, and later school/social re-entry; at follow-up, 62.3% versus 37.7% had disabilities and 57.7% versus 42.3% suffered mental trauma (all p ≤ 0.001). Disabilities affecting 225/227 people were skin-related; 34 were severely disabled but 193 had mild/moderate impairments. The prevalence of stress-related and mood disorders increased with burn extent. Treatment costs (mean USD-equivalents ∼$48, 977/patient, ∼$1192/%TBSA) increased with burn severity; however, the highest %TBSA, %STSG and f SASG categories accounted for <10% of total costs, whereas TBSA 41–80% accounted for 73.2%. Conclusions: Besides %TBSA, skin-graft requirements and burn scar contractures are complementary determinants of medium/long-term outcomes. We recommend further elucidation of factors that influence burn survivors' recovery, long-term physical and mental well-being, and quality of life.